Prediksi Financial Distress Model Ohlson’s: Peran Strategis Good Corporate Governance - Rieka Ayu Pradiska; Shinta Permata Sari (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
Financial distress is a company condition that reflects financial difficulties in a state of crisis before bankruptcy occurs. This study aims to analyze the effect of institutional ownership, managerial ownership, foreign ownership, independent commissioners, and gender diversity on the board on financial distress in basic materials sector companies listed on the Indonesia Stock Exchange for the period 2022-2024. The sampling technique used is purposive sampling with a sample size of 47 companies. Data are obtained from secondary data in the form of annual reports and data analysis use binary logistic regression. The results of this study indicate that institutional ownership and managerial ownership have an effect on financial distress. Meanwhile, foreign ownership, independent commissioners, and board gender diversity have no effect on financial distress.